The Negotiation of Muslimah Identity in Hijab Cosplay Phenomenon - Hasba, Hilda Balqis (UI Scholars Hub, 2022)
The identity of Muslimah is often associated with the idea of using hijab as a form of obedience to religion. This research examines the experiences of hijab women who use cosplay culture to represent their talents and creativity by creating a new culture. This research uses circuit of culture theory by Paul du Gay and Stuart Hall to analyze hijab cosplayers’ experiences in making hijab cosplay. The method used in this research is the qualitative research method and photo study technique to collect the data. This research shows that the process of creating hijab cosplay passes through identity, production, consumption, regulation, and representation that interplay and define one another. Therefore, hijab cosplay culture has become an arena for hijab women to create new meanings by uniting two discourses — cosplay and hijab —through daily practice. Their identity as hijab women influenced how hijab cosplay was produced and carried out. The costume and the cosplayer’s character relate to how hijab cosplayers consume a product. Some regulations regulate the activities of hijab cosplayers, such as the norm of hijab cosplay which comes from Islamic values and cosplay characteristics. The whole process is also represented by the appearance of hijab cosplayers in everyday life. Identitas muslimah seringkali dikaitkan dengan gagasan penggunaan hijab sebagai bentuk ketaatan terhadap agama. Penelitian ini bertujuan untuk memahami pengalaman muslimah yang menggunakan budaya cosplay untuk menyalurkan bakat dan kreativitas mereka dengan membuat budaya baru yaitu hijab cosplay. Peneliti menggunakan teori sirkuit budaya Paul du Gay dan Stuart Hall untuk menganalisis negosiasi muslimah dalam proses penciptaan hijab cosplay. Metodologi yang digunakan adalah metode penelitian kualitatif dan photo diary untuk mengumpulkan data dari lima informan. Hasil penelitian menunjukkan bahwa proses penciptaan hijab cosplay melalui proses identitas, produksi, konsumsi, regulasi, dan representasi yang saling mempengaruhi serta mendefinisikan satu sama lain. Budaya hijab cosplay menjadi arena bagi muslimah untuk menciptakan makna dengan menyatukan dua wacana — praktik cosplay dan hijab— melalui tindakan sehari-hari. Identitas sebagai muslimah mempengaruhi bagaimana hijab cosplay diproduksi dan dijalankan. Kostum dan karakter yang ditampilkan menunjukkan bagaimana hijab cosplayer mengonsumsi suatu produk. Terdapat regulasi yang mengatur kegiatan hijab cosplayer seperti norma hijab cosplay yang berasal dari nilai-nilai Islam dan karakteristik cosplay. Keseluruhan proses tersebut akhirnya merepresentasikan dan direpresentasikan oleh penampilan hijab cosplayer dalam kehidupan sehari-hari.